The effects of chief executive officer gender on firm labor investment efficiency - Kyoungwon Mo; Kyung Yun (Kailey) Lee (Borsa Istanbul Review, 2022)
This study examines the relationship between the gender of the chief executive officer (CEO) and a firm's labor investment efficiency. It evaluates whether firms led by a female CEO engage in more efficient labor-related investment decisions than those led by a male CEO. Using U.S. public companies as samples, we found that female CEOs make better employment-based investments by inhibiting a firm's overinvestment in labor. Furthermore, the results revealed that firms with a female CEO are more efficient at hiring employees. Additional analysis demonstrated that a female CEO's ability to reduce inefficiency in labor investments is greater for firms with more free cash flow. Thus, the results suggest that female CEOs are better at preventing suboptimal labor investment decisions, especially when hiring employees. This association is stronger when they have greater managerial power within a company.